Lipocalin 2 produces insulin resistance and can be upregulated by glucocorticoids in human adipose tissue. (15th May 2016) - Kamble, Prasad G.; Pereira, Maria J.; Sidibeh, Cherno O.; Amini, Sam; Sundbom, Magnus; Börjesson, Joey Lau; Eriksson, Jan W.
Abstract: The adipokine lipocalin 2 is linked to obesity and metabolic disorders. However, its role in human adipose tissue glucose and lipid metabolism is not explored. Here we show that the synthetic glucocorticoid dexamethasone dose-dependently increased lipocalin 2 gene expression in subcutaneous and omental adipose tissue from pre-menopausal females, while it had no effect in post-menopausal females or in males. Subcutaneous adipose tissue from both genders treated with recombinant human lipocalin 2 showed a reduction in protein levels of GLUT1 and GLUT4 and in glucose uptake in isolated adipocytes. In subcutaneous adipose tissue, lipocalin 2 increased IL-6 gene expression whereas expression of PPARγ and adiponectin was reduced. Our findings suggest that lipocalin 2 can contribute to insulin resistance in human adipose tissue. In pre-menopausal females, it may partly mediate adverse metabolic effects exerted by glucocorticoid excess. Highlights: This study demonstrates a role of lipocalin 2 in human adipose tissue metabolism. Dexamethasone induces lipocalin 2 gene expression in pre-menopausal females. Stromal vascular cells are major contributors of lipocalin 2 expression. Lipocalin 2 impairs basal and insulin-stimulated glucose uptake in adipocytes. Lipocalin 2 reduces PPARγ and adiponectin expression.